Lack of motor prediction, rather than perceptual conflict, evokes an odd sensation upon stepping onto a stopped escalator - Gomi, Hiroaki; Sakurada, Takeshi; Fukui, Takao (Frontiers in Behavioral Neuroscience, 2014)
When stepping onto a stopped escalator, we often perceive an “odd sensation” that is never felt when stepping onto stairs. The sight of an escalator provides a strong contextual cue that, in expectation of the backward acceleration when stepping on, triggers an anticipatory forward postural adjustment driven by a habitual and implicit motor process. . Here we contrast two theories about why this postural change leads to an odd sensation. The first theory links the odd sensation to a lack of sensorimotor prediction from all low-level implicit motor processes. The second theory links the odd sensation to the high-level conflict between the conscious awareness that the escalator is stopped and the implicit perception that evokes an endogenous motor program specific to a moving escalator. We show very similar postural changes can also arise from reflexive responses to visual stimuli, such as contracting/expanding optic flow fields, and that these reflexive responses produce similar odd sensations to the stopped escalator. We conclude that the high-level conflict is not necessary for such sensations. In contrast, the implicitly driven behavioral change itself essentially leads to the odd sensation in motor perception since the unintentional change may be less attributable to self-generated action because of a lack of motor predictions.